Keynesian government spending multipliers and spillovers in the Euro area - Tobias J. Cwik; Volker Wieland (Goethe University Frankfurt, Center for Financial Studies (CFS), 2009)
The global financial crisis has lead to a renewed interest in discretionary fiscal stimulus. Advocates of discretionary measures emphasize that government spending can stimulate additional private spending the so-called Keynesian multiplier effect. Thus, we investigate whether the discretionary spending announced by Euro area governments for 2009 and 2010 is likely to boost euro area GDP by more than one for one. Because of modeling uncertainty, it is essential that such policy evaluations be robust to alternative modeling assumptions and different parameterizations. Therefore, we use five different empirical macroeconomic models with Keynesian features such as price and wage rigidities to evaluate the impact of fiscal stimulus. Four of them suggest that the planned increase in government spending will reduce private spending for consumption and investment purposes significantly. If announced government expenditures are implemented with delay the initial effect on euro area GDP, when stimulus is most needed, may even be negative. Traditional Keynesian multiplier effects only arise in a model that ignores the forward-looking behavioral response of consumers and firms. Using a multi-country model, we find that spillovers between euro area countries are negligible or even negative, because direct demand effects are offset by the indirect effect of euro appreciation.
urn:nbn:de:hebis:30-72748
Keywords: E62; E63; H31; 330; Fiscal Policy; Fiscal Stimulus; Government Spending Multipliers; Model Uncertainty; Crowding-out; New-Keynesian Models; Finanzpolitik; Öffentliche Ausgaben; Multiplikator; Spillover-Effekt; Keynesianismus; EU-Staaten